1979
DOI: 10.1172/jci109325
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between the Doses of Cholecystokinin or Caerulein-Stimulating Exocrine and Endocrine Responses in Perfused Isolated Rat Pancreas

Abstract: A B S T R A C T The effects of highly purified natural porcine cholecystokinin (CCK) and synthetic caerulein on the rate of flow of pancreatic juice, the rate of output of amylase, and the rate of release of immunoreactive insulin (IRI) and immunoreactive glucagon (IRG) were simultaneously investigated in the isolated perfused rat pancreas.The maximal flow rate of pancreatic juice was obtained with concentrations of CCK ranging from 0.5 to 10 mU/ml, whereas amylase output was maximal at CCK concentrations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Recently, several potent CCK antagonists with a structure of 4-benzamido-N,N-di-alkyl-glutaramic acid have been synthesized [18,19,21,22], Among them, CR 1409 was found to be the most potent antagonist of CCK action on the pancreas, that is 3-4 times more potent than CR 1392 (K; 0.6 pM; present study), with the Kj for the pancreatic CCK receptor being 0.13-0.2 pM [19,21,22], In the present study, however, CR 1409 at a concentration of 1 mM caused amylase release of 107.4 ± 0.6% of the initial content in the acini, whereas the same concentration of CR 1392 (1 mM) caused an increase in amylase release up to 19.9 ± 2.3% of initial content. All the acini incubated with 1 mM CR 1409 for 30 min were unable to exclude trypan blue, whereas only few acini incu bated with 1 mM CR 1392 were stained blue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several potent CCK antagonists with a structure of 4-benzamido-N,N-di-alkyl-glutaramic acid have been synthesized [18,19,21,22], Among them, CR 1409 was found to be the most potent antagonist of CCK action on the pancreas, that is 3-4 times more potent than CR 1392 (K; 0.6 pM; present study), with the Kj for the pancreatic CCK receptor being 0.13-0.2 pM [19,21,22], In the present study, however, CR 1409 at a concentration of 1 mM caused amylase release of 107.4 ± 0.6% of the initial content in the acini, whereas the same concentration of CR 1392 (1 mM) caused an increase in amylase release up to 19.9 ± 2.3% of initial content. All the acini incubated with 1 mM CR 1409 for 30 min were unable to exclude trypan blue, whereas only few acini incu bated with 1 mM CR 1392 were stained blue.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated perfused rat pancreas was prepared as reported previously [21]. The perfusate used was a Krcbs-Ringer bicarbonate solution containing 4.6% dextran T-70, 0.25% bovine plasma albumin, and 8.3 mM glucose.…”
Section: Isolated Perfused Pancreasmentioning
confidence: 99%
“…In addition to these actions on gastrointestinal functions, studies both in vivo and in vitro in several species have indicated that CCK stimulates insulin release (4)(5)(6)(7)(8)(9). We lhave recently developed a sensitive and specific bioassay for measuring plasma CCK levels in humans (10, 1 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies in rats using natural porcine CCK [2. 13] or cerulein [8,13,14], and in vivo experiments using natural porcine CCK [15] have shown that the insulinotropic effect of CCK is glu cose dependent. This is confirmed in the present study in that even the highest levels of CCK-8 had no effect on insulin release at a perfusate glucose concentration of 2.8 mM ( fig.…”
Section: Discussionmentioning
confidence: 99%